Combination of lamivudine and adefovir without hepatitis B immune globulin is safe and effective prophylaxis against hepatitis B virus recurrence in hepatitis B surface antigen–positive liver transplant candidates. Issue 3 (11th March 2013) - Gane, Edward J.; Patterson, Scott; Strasser, Simone I.; McCaughan, Geoffrey W.; Angus, Peter W.
<x xml:space="preserve">Abstract</x> Without effective prophylaxis, liver transplantation for hepatitis B virus (HBV)–related liver disease is frequently complicated by severe and rapidly progressive HBV recurrence. Combination prophylaxis with hepatitis B immune globulin (HBIG) and lamivudine (LAM) reduces long‐term recurrence rates below 10%; however, HBIG is costly and inconvenient to administer. We, therefore, conducted a multicenter, prospective study of outcomes with an HBIG‐sparing regimen of LAM plus adefovir dipivoxil (ADV) initiated at the time of listing for liver transplantation and continued after transplantation. Twenty‐six patients were recruited into this study at the time of listing for transplantation, and 20 subsequently underwent transplantation. Twelve of the 26 patients had LAM exposure before the study baseline, but none had LAM resistance. The median HBV viral load before the institution of antiviral therapy was approximately 4.0 log10 IU/mL (range=2.3–7.5 log10 IU/mL). To the 20 patients who underwent transplantation, 800 IU of intramuscular HBIG was given immediately after transplantation and daily for 7 days only (total HBIG dose=6400 IU). All transplant patients remained alive without HBV recurrence (they were negative for hepatitis B surface antigen, and HBV DNA was undetectable) after a median follow‐up of 57 months after transplantation (range=27–83 months). The median serum creatinine level in these patients rose from 81 to 119 μmol/L over the course of the study. No patient required dose reduction or cessation. After the completion of this prospective study, the regimen was modified so that no perioperative HBIG was administered if the pretransplant serum HBV DNA level was suppressed below 3 log10 IU/mL. Another 28 patients with HBV‐related liver disease underwent transplantation (18 without HBIG). All remained alive and well without HBV recurrence after a median follow‐up of 22 months after transplantation (range=10–58 months). In conclusion, a combination of LAM and ADV initiated at the time of wait listing provides safe and effective protection against recurrent HBV infection without the high costs and inconvenience associated with long‐term HBIG therapy. Liver Transpl 19:268–274, 2013. © 2013 AASLD.